EFFECT OF GENETIC MAKEUP AND SEASON ON FERTILITY AND HATCHABILITY OF CHICKEN VARIETIES OF RURAL FARMING - D. Gandhimathi; M. Murugan; S.C. Edwin (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Data of 229 hatches of commercial country chicken hatchery for a period of four years from 2017-2020 was collected and analyzed to study the effect of genetic makeup and season on fertility and hatchability in chicken varieties developed for rural chicken rearing viz., Aseel cross, Kaveri, Grampriya and Vanaraja. Kaveri chicken varieties recorded significantly higher fertility of 85.04 per cent (P<0.01) followed by Aseel cross, Gramapriya and Vanaraja which are comparable in fertility values of 81.68, 81.33 and 82.80 per cent, respectively. In terms of fertile and total hatchability, Kaveri recorded significantly higher values of 94.16 and 80.08 per cent than other varieties. Winter and North East Monsoon seasons recorded significantly higher value of 89.39 and 87.91 per cent in Kaveri, 85.22 and 83.84 per cent in Aseel Cross and 84.85 and 86.42 per cent in Gramapriya. On the other hand, summer season recorded the lowest fertility rates in all the chicken varieties.